The Effects of Malaria in Pregnancy on Neurocognitive Development in Children at 1 and 6 Years of Age in Benin: A Prospective Mother–Child Cohort. (23rd July 2021) - Garrison, Amanda; Boivin, Michael J; Fiévet, Nadine; Zoumenou, Roméo; Alao, Jules M; Massougbodji, Achille; Cot, Michel; Bodeau-Livinec, Florence
Abstract: Background: Malaria in pregnancy (MiP) contributes significantly to infant mortality rates in sub-Saharan Africa and has consequences on survivors, such as preterm birth and low birth weight. However, its impact on long-term neurocognitive development in children remains unknown. Methods: Our prospective cohort included pregnant women and their live-born singletons from the Malaria in Pregnancy Preventive Alternative Drugs clinical trial. MiP was assessed using microscopy and real-time quantitative polymerase chain reaction (qPCR). Neurocognitive development in children was assessed using the Mullen Scales of Early Learning and the Kaufman Assessment Battery for Children, 2nd edition (KABC-II), at 1 and 6 years of age, respectively. Results: Of 493 pregnant women, 196 (40%) were infected with malaria at least once: 121 (31%) with placental malaria diagnosed by qPCR. Multiple linear regression B-coefficients showed that impaired gross motor scores were associated with MiP at least once (−2.55; confidence interval [95% CI]: −5.15, 0.05), placental malaria by qPCR (−4.95; 95% CI: −7.65, −2.24), and high parasite density at delivery (−1.92; 95% CI: −3.86, 0.02) after adjustment. Malaria and high parasite density at the second antenatal care visit were associated with lower KABC-II Non-Verbal Index scores at 6 years (−2.57 [95% CI: −4.86, −0.28] and −1.91 [−3.51, −0.32]), respectively. Conclusions: This prospective cohort study provides evidence that MiP, particularly late term, could have important negative consequences on child development at 1 and 6 years of age. Mechanisms behind this association must be further investigated and diagnostic methods in low-income countries should be strengthened to provide adequate treatment. Clinical Trials Registration: NCT00811421. Abstract : This paper provides the first evidence of an association between late-term peripheral and placental malaria in pregnancy and impaired neurocognitive development in offspring at 1 and 6 years of age in Benin, sub-Saharan Africa.